Removal of Heavy Metals (Fe3+, Cu2+, Zn2+, Pb2+, Cr3+ and Cd2+) from Aqueous Solutions by Using Hebba Clay and Activated Carbon - Shama,S.A. (2010)
The adsorption capacity of hebba clay and activated carbon towards (Fe3+, Cu2+, Zn2+, Pb2+, Cr3+, Cd2+) metal ions was studied. The adsorption capacity was investigated by batch experiment. The effect of weight of hebba was studied and the results showed that the removal percentages increased as the weight of sorbent increased. The effect of contact time was also studied and the results showed that the removal percentages increased as the contact time increased. The effect of pH of the solution was also studied and the removal percentages for (Cu2+, Zn2+ and Cd2+) were affected slightly by changing the pH value, but for (Fe3+, Pb2+ and Cr3+) the effect was higher. Also, the effect of initial concentration of metal ions was studied at four different concentrations (5, 10, 30, 50 mg/L); in case of metal ions (Cu2+, Zn2+ and Cd2+), the removal percentages increased by increasing initial concentration. But for the other metal ions it decreased. The order of increasing removal percentages of metal ions at pH=4.86, concentration of metal ions 30 mg/L, and after four hours of shaking, was (Pb2+ < Cu2+ < Cd2+ < Cr3+ < Zn2+ < Fe3+). But in the case of activated carbon, the order was Cd2+ < Zn2+ < Cu2+ < Pb2+ < Cr6+ < Fe3+.